Pengaruh Brand Image, Brand Ambassador, Dan Halal Awareness Terhadap Keputusan Pembelian Skincare Berlabel Halal - Kurnia, Tri; M.Sc., PURWO ADI WIBOWO, S.E., (JEBIM Prima, 2023)
Halal lifestyle continues to experience improvement from time to time. One sector that has experienced a drastic increase is halal skincare or skincae labeled halal. Various halal skincare brands on the market such as wardah, makeover somethink. With the increasing prevalence of skincare labeled halal, companies must prioritize not only quality but also external factors that support consumer purchasing decisions. This study aims to determine the effect of brand image, brand ambassador, and halal awareness on the purchase of skincare labeled halal. The research was conducted using quantitative research methods with random sampling method. From the data collected, it will be processed to find out brand image, brand ambassadors, and halal awareness of purchasing skincare labeled halal. Key words: Brand image, brand ambassador, halal awareness